Characterization of the head-to-trunk orientation with handheld optical 3D apparatus based on the fringe projection technique - Pavlovčič, Urban; Diaci, Janez; Možina, Janez; Jezeršek, Matija (Biomedical engineering online, 2013)
Background Knowing the orientation of the head is important in many fields, including medicine. Many methods and measuring systems exist, but usually they use different markers or sensors attached to the subject’s head for head orientation determination. In certain applications these attachments may represent a burden or a distraction to the subject under study which may have an unfavourable impact on the measurement. We propose a non-contact optical method for head-to-trunk orientation measurement that does not require any attachments to the subject under study. Methods An innovative handheld 3D apparatus has been developed for non-invasive and fast 3D shape measurements. It is based on the triangulation principle in combination with fringe projection. The shape of the subject’s upper trunk and head is reconstructed from a single image using the Fourier transform profilometry method. Two shape measurements are required to determine the head-to-trunk orientation angles: one in the reference (neutral) position and the other one in the position of interest. The algorithm for the head-to-trunk orientation angle extraction is based on the separate alignment of the shape of the subject’s upper trunk and head against the corresponding shape in the reference pose. Single factor analysis of variance (ANOVA) was used for statistical characterisation of the method precision. Results The method and the 3D apparatus were verified in-vitro using a mannequin and a reference orientation tracker. The uncertainty of the calculated orientation was 2°. During the in-vivo test with a human subject diagnosed with cervical dystonia (aged 60), the repeatability of the measurements was 3°. In-vitro and in-vivo comparison was done on the basis of an experiment with the mannequin and a healthy male (aged 29). These results show that only the difference between flexion/extension measured angles was statistically significant. The differences between means were less than 1° for all ranges. Conclusions The new non-contact method enables the compensation of the movement of the measuring instrument or the subject’s body as a whole, is non-invasive, requires little additional equipment and causes little stress for the subject and operator. We find that it is appropriate for measurements of the head orientation with respect to the trunk for the characterization of the cervical dystonia.